Predictors of accountability outcomes in nonprofit organisations: an empirical investigation / Jamaliah Said, Nurul Aisyah Zainal Abidin and Noraini Mohd Nassir - Said, Jamaliah; Zainal Abidin, Nurul Aisyah; Mohd Nassir, Noraini (Faculty of Accountancy, 2013)
This study examined factors influencing accountability outcomes by non-profit Organisations (NPOs). Four factors identified in strategic management literature were examined; mission based management practices, budgeting practices. financial reporting practices and financial priorities. Analysis of finding from questionnaire reveived from top level management of NPOs discovered that mission based management practices, financial reporting practices, financial priorities significantly related to the level of accountability among NPOs. The finding of this study provides indication that for NPOs to demonstrate high level of accountability, they need to have mssion based management practices, financial reporting practices and adopt adequate level of financial priorities.